The Impact of Disasters on Stress Levels of Caregivers of Children with Special Needs: A Comparative Study - Erturan, Sinem; Başaran, Zekiye; Burak, Mustafa; Elbasan, Bulent (My University, 2024)
Aim: Caring needs of children with special needs increase the stress levels of caregivers for many reasons. The aim of this study was to examine, compare, and provide recommendations regarding the stress levels, factors influencing stress levels, and coping strategies among caregivers of both healthy and special needs children during disaster periods. Method: This research was planned as a cross-sectional study. The survey, which was created in an electronic environment, disseminated to as many people as possible across the country via e-mail, various communication networks, and social media. After the demographic information of 261 caregivers were recorded, the Depression Anxiety Stress Scale 21, the Caregiver Strain Index, and the Ways of Coping Inventory Questionnaire were administered. Results: While the stress level was high (Mean±SD:7.67±3.98) in the caregivers of children with special needs, this level was within the normal limits (Mean±SD:6.44±3.61) in the caregivers of healthy children. There was a significant difference between the groups (p:0.009). In terms of coping with stress, caregivers of children with special needs were found to prefer emotion-focused/passive approaches, and there was a difference between the groups (p:0.000). Conclusion: The restrictive conditions during disaster period can impact the mental health of caregivers of special needs children, and there are several factors involved in this process. In line with this, we believe that specific policies and strategies need to be developed to support the mental health of caregivers of special needs children during extraordinary situations such as disaster scenarios.
Keywords: Child; mental health; Caregivers; natural disasters; children with special needs.